Examining the West African Monsoon circulation response to atmospheric heating in a GCM dynamical core. (25th January 2017) - Chadwick, R.; Martin, G.M.; Copsey, D.; Bellon, G.; Caian, M.; Codron, F.; Rio, C.; Roehrig, R.
Abstract: Diabatic heating plays a crucial role in the formation and maintenance of the West African Monsoon. A dynamical core configuration of a General Circulation Model (GCM) is used to test the influence of diabatic heating from different sources and regions on the strength and northward penetration of the monsoon circulation. The dynamical core is able to capture the main features of the monsoon flow, and when forced with heating tendencies from various different GCMs it recreates many of the differences seen between the full GCM monsoon circulations. Differences in atmospheric short‐wave absorption over the Sahara and Sahel regions are a key driver of variation in the models' monsoon circulations, and this is likely to be linked to how aerosols, clouds and surface albedo are represented across the models. The magnitude of short‐wave absorption also appears to affect the strength and position of the African easterly jet (AEJ), but not that of the tropical easterly jet (TEJ). The dynamical core is also used here to understand circulation changes that occur during the ongoing model development process that occurs at each modeling centre, providing the potential to trace these changes to specific alterations in model physics. Key Points: The main features of the West African monsoon flow can be reproduced in a dynamical core Atmospheric shortwave absorption over the Sahara and Sahel is a major driver of differences between models. A dynamical core can be used to understand circulation changes in relation to model development.